Harnessing mitochondrial metabolism and drug resistance in non-small cell lung cancer and beyond by blocking heat-shock proteins - Parma, Beatrice; Wurdak, Heiko; Ceppi, Paolo (Drug Resistance Updates, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide, with non-small cell lung cancer (NSCLC) being the predominant histological subtype. Despite the emergence of targeted and immune-based therapies that have considerably improved the clinical outcomes of selected patients, the overall NSCLC survival rate remains poor. NSCLC patients experience clinical relapse mainly because of chemoresistance. One promising therapeutic approach is targeting specific molecular vulnerabilities that are associated with the metabolic reprogramming of cancer cells. This strategy relies on evidence that cancer cells rewire their metabolism to sustain their uncon-trolled growth as well as invasive and metastatic properties, promoting adaptive resistance to chemo-radiotherapy. A critical component of this malignant transformation is the increased dependency on high levels of heat shock proteins (HSPs), which support the elevated protein folding demand and quality control of misfolded oncoproteins. Here, we provide an overview of the literature on metabolism reprogramming, dereg-ulation of mitochondrion and on the role of HSPs in promoting malignancy in lung and other cancer types. A particular focus is dedicated to the role of mitochondrial HSP60 (HSPD1) in NSCLC metabolism and drug resistance for the potential development of new resistance-defying anti-HSP drugs.
CRIS-Team WoS Importer:2022-11-25